Measure of human resource management practices: psychometric properties and factorial structure of the questionnaire PRH-33 - Boada Grau, Joan; Gil Ripoll, Carme (Anales de Psicología / Annals of Psychology, 2011)
In the present article we study the psychometric properties of a scale (PRH-33) designed to determine human resources practices in organizations. To do so, we administered an initial pool of 97 items related to these practices. 374 company directors from different manufacturing sectors participated. The exploratory factorial analysis of the 97 items revealed a structure consisting of two factors: development (the professional growth of individuals) and training (the use of processes, procedures and tools). To obtain a shorter scale, we selected the 33 items with the highest saturations in the aforementioned factors. The two subscales obtained had the necessary level of reliability. These results show that the present scale (PRH-33) is a highly useful tool for correctly evaluating organizational human resources practices.